IMPLEMENTASI RETRIBUSI PARKIR DI TEPI JALAN UMUM - Selvi Nurdiana E.42008057 (FISIP Universitas Tanjungpura Pontianak, 2012)
The title of this research is “retribution implementation park by the side of public road in Nanga Pinoh District Office in Melawi Regency”. The title of this research concern was retribution implementation park by the side of public road which still not yet 100% can reach the retribution goals which have been specified. This research is qualitative research. Conclusion in this research is implementators do not know big of tariff park which as describe in by law of concerning retribution park by the side of public road, still the lack of resources of human being owned from its amount facet that is field worker, still the lack of resources equipments as supported that is farm park narrow, disposition / expert attitude park which do not use the equipment of during parking implementation. For the recommendation of retribution implementation. For the recommendation of retribution implementation park by the side of public road give the congeniality and understanding to society of concerning content of by law of concerning elementary tariff of parking of through socialization earn also by enhancing certain location nameboard hit the tariff park, for the resources of human being can be condused with the worker addition park the field, resources finance by conducting budgeting for the equipment of worker in field and specify the retribution goals adapted for by a field condition, disposition of field executor can be improved by giving reward, and conduct the improvement of coordination usher the implementator policy. Keyword : Policy, Retribution Park and Contribution PAD.